PROFIL PROTEIN TIROSIN KINASE DALAM SEMINAL PLASMA DOMBA MERINO DENGAN TEKNIK SODIUM DODECYL SULPHATE POLYACRILAMIDE GEL ELECTROPHORESIS - Nawangwulan, Tantri; Madyawati, Sri Pantja; Plumeriastuti, Hani; Sardjito, Trilas; Susilowati, Suherni; Safitri, Erma (Ovozoa: Journal of Animal Reproduction, 2018)
The aim of this study was to find out protein tyrosine kinase profile in Merino Sheep seminal plasma. This study consist of collecting semen of Merino Sheep containing plasma and spermatozoa, the separation between seminal plasma and spermatozoa, then tyrosine kinase analysis using Sodium Dodecyl Sulphate Polyacrilamide Gel Electrophoresis (SDS-PAGE). Semen was collected by artificial vagina and then centrifugated for 40 minutes at 4000 rpm to separated seminal plasma and spermatozoa. Protein was analyzed using SDS-PAGE, to separate each protein based on their molecular weight. The result showed that there were 13 protein bands in 3 seminal plasma samples with an average 149,63 kDa, 139,7 kDa, 114,97 kDa, 109,3 kDa, 97,33 kDa, 93,83 kDa, 86,23 kDa, 77,6 kDa, 64,6 kDa, 52,3 kDa, 41,93 kDa, 38,13 kDa, and 34,5 kDa. In conclusion, it is believed that tyrosine kinase located on the sixth band with molecular weight 93,83 kDa.